Relationship between work-family conflict and quality of life: an investigation into the role of social support - Md Sidin, Samsinar; Sambasivan, Murali; Ismail, Izhairi (Emerald Group Publishing Limited, 2010)
Purpose – The main purpose of this study is to link work-family conflict, quality of work and non-work lives, quality of life and social support (supervisor and spouse supports). Specifically, it seeks to address three different roles of social support that have theoretical and empirical support and the mediating roles of quality of work life and quality of non-work life. Design/methodology/approach – The SEM-based approach has been used to study supervisor and spouse supports as moderators between work-family conflict and quality of life; independent variables of work-family conflict; independent variables of quality of life. The study has been carried out in Malaysia. Findings – The main findings are: work-family conflict has relationship with quality of life; quality of work life and non-work life are “partial” mediators between work-family conflict and quality of life; and, among the various roles of social support, its role as an independent variable of quality of life gives the best results. Research limitations/implications – The research is based on a cross-sectional study conducted in Malaysia and addresses only the spouse and supervisor supports as components of social support. Originality/value – The research has developed a comprehensive model linking work-family conflict, quality of work and non-work lives, and quality of life and has studied the role of social support.